Physicochemical evaluation of Mangifera indica L. fruits c.v Vallenato preserved in modified atmosphere to extend its quality - Fernández Varela, Aldo Alexander; Reales Alfaro, Juan Guillermo (Rev. Téc. Fac. Ing. Univ. Zulia)
In order to evaluate the influence of modified atmospheres on physicochemical aspects related to the conservation of mango variety vallenato packaging films used for low density polyethylene calibers 2 and 3 mils and three gas mixtures (3% O2-3% CO2-94% N2, 4%O2-7% CO2-89% N2, 5%O2-5% CO2-90% N2) for a completely randomized experimental design of six treatments (T1, T2, T3, T4, T5 and T6) of which its was possible evaluate physicochemical aspects in three (T1, T3 and T5) to preserve fruit without chilling injury after sixteen days. The storage temperature was 12°C, relative humidity of 63%, 30 days, plus nine days at 20°C. With modified atmosphere packaging reduced the occurrence of soluble solids compared to the fruits witnesses, did not influence very significantly in pH, only after thirty days after the acidity thirty-three days falls much more in the controls and lower in T5 on day 39. The film that presented a better behavior when gas exchange was the caliber 2 mils, which was retained for longer than fruit characteristics with the gas mixture of 5% O2-5% CO2-90% N2.